DETERMINATION OF ACETIC AND PROPANOIC ACIDS CONCENTRATION IN NIGERIAN KEROSENE - ISAAC KAYODE ADEGUN; OLUWATOSIN ADEDAMOLA ADESOYE; ADIO-YUSUF SELIA IYAGBA; DAVID ADEBOLA ADETORO (Journal of Engineering Studies and Research)
The paper aims to determine acetic and propanoic acid concentrations in some selected samples of kerosene used in Nigeria. The Armfield Liquid-Liquid Extraction Unit was employed to carry out the study. Distilled water and kerosene samples from five different sources were used for the investigation. The parameters taken into consideration during the course of the experiments were time, thermal conductivity, temperature, flow rates and concentration of the acid. It was deduced from the research that the temperature and the conductivity decreased with significant decrease in concentration of the acid and vice versa. The results gotten from the extraction of the kerosene samples also showed that sample A, sample D, and sample E did not contain acetic acid while sample B and sample C had traces of acetic acid, with sample C having traces of propanoic acid. After comparing the values with the standard classification of acetic acid, it was discovered that the concentration of both acetic and propanoic acid in the samples were not significantly sufficient to harm human beings.